Tetrathienylethene-based porous framework composites for boosting photocatalytic antibacterial activity - Si Ma; Yintung Lam; Le Shi; Jian Yang; Kun Wang; Bo Yu; Chiwai Kan; Bin Fei; John H. Xin; Kaikai Ma; J. Fraser Stoddart; Zhijie Chen (Proceedings of the National Academy of Sciences, 2025)
In order to reduce the risk of high-threat pathogens, a photocatalytic antibacterial method with a reputation for high efficiency and sustainability has attracted widespread attention. Recently, metal-organic frameworks (MOFs) have emerged as desirable platforms for photocatalytic applications by virtue of their structural diversity and functional adjustability. Herein, we report that we have synthesized a stable and photosensitive zirconium-based MOF (Zr-MOF) with a photoactive tetrathienylethene-based organic linker, Zr-TSS-1. Compared with all-carbocyclic Zr-MOF counterparts, Zr-TSS-1 shows a substantial improvement in visible-light harvesting and free-carrier generation, enabling it to be a promising candidate for photocatalytic antibacterial applications. In order to validate the advantages of this framework as an antibacterial protective material, a composite was fabricated by incorporating robust Zr-TSS-1 onto sustainably accessible bacterial cellulose (BC) using an in situ growth method. This composite exhibits near-complete lethality toward typical Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus within 1 h under mild irradiation and preserves outstanding antibacterial capability after five cycles of reutilization. In addition, the high biocompatibility is confirmed by the low cytotoxicity toward human skin fibroblast, suggesting its potential for biomedical and healthcare applications. This research demonstrates the efficacious integration of a purposely designed photosensitive porous framework onto a sustainable substrate for synergistic functionality, paving a practical way for the development of the next-generation high-efficiency antimicrobial technology.